66 Impact of using the papworth haemostatic checklist on cardiac surgery patient outcomes at queen elizabeth hospital birmingham, united kingdom. (6th June 2022) - Lad, Tanvi; Bhatt, Shreya
Abstract : Background: Mediastinal bleeding is a common, major complication of cardiac surgery. Treatment requires patients to return to theatre to identify the source of bleeding which is associated with significant mortality and immediate postoperative morbidity (notably acute renal failure, infection, and stroke) as well as the risks of allogeneic blood product use, mechanical ventilation and longer ICU stay.(1, 2) The Papworth Haemostatic Checklist (PHC) is an effective tool to reduce postoperative mediastinal bleeding in cardiac surgery by systematically checking surgical sites and coagulation status before sternal wire insertion.(3–5) A pilot study showed significantly reduced rates of bleeding, re-exploration and blood product consumption in 5000 patients undergoing cardiac surgery over a 2-year period. The checklist's success won a nomination for a national patient safety award. Aims and objectives: This quality improvement project (QIP) aims to improve patient outcomes at Queen Elizabeth Hospital Birmingham (QEHB) by implementing the PHC. Methods: We retrospectively extracted data from electronic health records for 150 patients undergoing cardiac surgery from Dec'20-Aug'21. Baseline demographics and postoperative outcomes (mediastinal blood loss, re-exploration and blood product transfusion) were analysed.(6) Results: Median blood loss 12 h post-operation was 429.81 ml (IQR 243.75). 3.33% underwent reexploration for bleeding and 46.6% received blood products. Median ICU stay was 3 days (IQR 2) and 2% of patients died. Conclusion: This first cycle of the QIP showed significant complications from bleeding in terms of patient outcomes and cost to QEHB.6 Following discussion, the department decided to implement the checklist to improve this. Our next steps are to familiarise operating teams with the PHC through posters and staff briefings. The anaesthetics team will be responsible for going through the checklist during the operation. We will subsequently undertake a second cycle of data collection and analysis for a further 150 patients. Conflict of Interest: -